Investigation of luminescence and scintillation properties of a ZnS-Ag/6LiF scintillator in the 7-295 K temperature range - Mikhailik, V; Henry, S; Horn, M; Kraus, H; Lynch, A; Pipe, M (2013)
The luminescence and scintillation properties of ZnS-Ag/6LiF where studied in the 7-295 K temperature range to evaluate the suitability of the scintillator for neutron detection at very low temperature (<1 K). It is shown that decrease of temperature has little effect upon principal luminescence and scintillation characteristics of ZnS-Ag: the changes of emission intensity are small for photoexcitation and negligible for excitation with α-particles. The recombination kinetics of the scintillation decay exhibits modest shortening of the fast decay time constant, from 4.52 to 3.35 μs with cooling to 10 K. It is concluded that ZnS-Ag/6LiF is a promising scintillator for cryogenic application. © 2012 Elsevier B.V. All rights reserved.